2015
DOI: 10.1167/iovs.14-15654
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Age-Related Changes in the Biomechanical Properties of Rabbit Lens Using a Coaligned Ultrasound and Optical Coherence Elastography System

Abstract: The results demonstrate that the US-OCE system can be used for noninvasive analysis and quantification of lens biomechanical properties in situ and possibly in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 42 publications
3
72
0
1
Order By: Relevance
“…However, for imaging tissues in situ both ultrasound stimulation and OCT beam are preferable to be on the same side. Such design was incorporated in our recent work to assess the age-related changes in the biomechanical properties of the crystalline lens in situ (Wu et al, 2015). …”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for imaging tissues in situ both ultrasound stimulation and OCT beam are preferable to be on the same side. Such design was incorporated in our recent work to assess the age-related changes in the biomechanical properties of the crystalline lens in situ (Wu et al, 2015). …”
Section: Results and Disscussionmentioning
confidence: 99%
“…The radiation force can be generated not only inside the tissue but also at the tissue surface or at the tissue boundaries where there is a significant difference in the acoustic impedance. Tissue excitation and surface deformation measurements have been used in elastography of skin (Li et al, 2012a, Li et al, 2012b, Coutts et al, 2006, Kirkpatrick et al, 2006), cornea (Tanter et al, 2009, Twa et al, 2014), crystalline lens (Wang et al, 2013, Manapuram et al, 2011, Wu et al, 2015), bladder wall (Li et al, 2014, Nenadic et al, 2013) and other potential applications (Sarvazyan, 2010). However, in all of these applications, the depth inhomogeneity of the tissue plays an important role in its mechanical response.…”
Section: Introductionmentioning
confidence: 99%
“…In temporal analysis methods, an external stimulus is used to remotely induce a displacement in the sample, and a phase-sensitive method, typically co-focused with the stimulus, is utilized to monitor the localized temporal response of surface deformations. Again, spectral decomposition can be used to quantify the viscoelasticity of the measured position [64,191], as well as the depth-resolved viscoelasticity [64]. Wu et al showed that spectral analysis of the displacement response of rabbit crystalline lenses of different ages in response to ARF in situ could reconstruct the lens viscoelasticity [191].…”
Section: Surface Elastic Wave Methods and Applicationsmentioning
confidence: 99%
“…Again, spectral decomposition can be used to quantify the viscoelasticity of the measured position [64,191], as well as the depth-resolved viscoelasticity [64]. Wu et al showed that spectral analysis of the displacement response of rabbit crystalline lenses of different ages in response to ARF in situ could reconstruct the lens viscoelasticity [191]. Expanding upon the displacement response spectral analysis, Wang et al showed the feasibility of a utilizing the surface temporal displacement profile to distinguish layered phantoms [87], which, when combined with an analytical model [64], could provide the depth-resolved viscoelasticity distribution from only the surface temporal profile.…”
Section: Surface Elastic Wave Methods and Applicationsmentioning
confidence: 99%
“…In an optical coherence elastography (OCE) application, the OCT unit is used for detection of elastic vibration, and different excitation sources are employed to generate an elastic wave in soft materials, including non-contact focused air-puff device [9,10] and ultrasonic transducer [1114], and contact mechanical wave driver [15] and piezoelectric actuator [16,17]. The noncontact air-puff device has conveniently detected the elastic modulus of the cornea [9].…”
mentioning
confidence: 99%